Booking System for Permai Seri Homestay with One Time Password (OTP) and Inactive User Data Deletion - Ruslan, Nursyakirah; Rahim, Nordiana (Applied Information Technology And Computer Science, 2025)
This project develops a secure, user-friendly booking system for Permai Seri Homestay in Ampang, Selangor, to replace the current methods using Facebook and WhatsApp, which lack security and efficient guest data management. The system includes One-Time Password (OTP) authentication, data deletion for inactive users. Built using the Agile Model, it features components for both customers and owners, including booking and house management. The system improves booking security, maintains an active user base, and enhances data protection. In conclusion, the project successfully creates a secure, efficient booking system that simplifies operations and safeguards guest information for Permai Seri Homestay.